From Therapy to Teaching: How to Use Islamic Psychotherapy in Religious Education For Student Well-Being - Yunita Furi Aristyasari; Abdul Mustaqim; Ichsan, Ichsan (Scidac Plus, 2026)
This study aims to establish a conceptual framework for incorporating Islamic psychotherapy into Islamic religious education as a preventive and non-clinical method for enhancing students' emotional and behavioral well-being. The study addresses the rising incidence of emotional and behavioral issues among children and adolescents amid swift modernization. Despite the traditional emphasis on moral and spiritual growth in Islamic education, there remains an absence of a comprehensive framework that incorporates psychological methodologies alongside Islamic pedagogical principles to tackle modern mental health issues. This study utilizes a conceptual-analytical framework grounded in review, content analysis, and comparative-conceptual analysis. The research integrates classical Islamic psychological principles, current Islamic psychotherapy literature, and contemporary cognitive-behavioral theory through the utilization of authoritative Islamic texts, peer-reviewed psychological research, and secondary empirical data concerning student mental health. The results delineate three categories of psychotherapy integration into Islamic religious education: traditional, modified, and integrative approaches. The integrative model, defined by a cognitively focused and spiritually grounded framework influenced by Abu Zayd al-Balkhi's work, stands out as the most comprehensive model for educational environments. This methodology integrates cognitive restructuring, emotional regulation, and moral habituation within Islamic spiritual beliefs, while upholding distinct ethical boundaries between educators and clinical therapists. The study suggests that Islamic psychotherapy can be pedagogically adapted to enhance students' psychological and spiritual growth without converting educational institutions into clinical environments. The proposed framework contributes to Islamic psychology and religious education by offering a culturally grounded and ethically appropriate approach to promoting student well-being.